The Problem Faced by Freshmen Students of English Education Department In Writing English Paragraph - Widi Syahtia Pane; Aranxtha Olivia Sanchez (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
This research is aimed to reveal new students’ obstacle in doing paragraph writing; from the pre-writing activity, writing process and also editing. Descriptive qualitative was done to conduct this research. The researchers used interview to collect data and also to verify the result of the data by doing observation on student’s work in writing process. After the results revealed, it is hoped that they are useful for teachers and also students to know the problem they probably face in paragraph writing teaching and also learning, therefore they can anticipate the problem and find solution to those obstacles. The result of this research shows that the students face difficulties in determining topic, main idea, and also the rest of content, grammatical error, vocabulary difficulty, making brainstorming phase, forgot or confused to determine conclusion, punctuation, translation and coherence problem, mistake in language (sentence structure, spelling and word choice).